Java projects learn the fundamentals of Java 11 programming by building industry grade practical projects - Verhas, Peter (Packt, 2018)
Java is one of the software languages most commonly used by programmers and developers. This book covers essential concepts in Java by showing you how to implement them in various applications. You'll learn about Java 18.9's newest features and develop the skills required for building robust, easily scalable, and maintainable code in Java
Keywords: Java Standard Edition 11; Java (Computer program language)